Study of structural properties of barium ferrite compounds and barium ferrite compounds doped with ( Co) and (Ti) by using solid state reaction and deposited thin films of these compounds by pulsed laser deposition (PLD). - Hussain, Saleem Azara (Al-Qadisiyah Journal of Pure Science, 2017)
In this research we prepared polycrystalline hexagonal ferrite compounds by solid state reaction methods by using iron and Barium Oxides . We deduce the suitable temperature of reaction and the cooling condition according to phase diagram of barium ferrite system, then we prepared thin film barium ferrite by pulsed laser deposition , also we studied the effect of some of factors like the annealing temperature and substrate temperature on the crystal structure of the prepared films.